ANALISIS PEMASARAN TERNAK KAMBING KALIGESING (STUDI KASUS DI DESA PANDANREJO, KECAMATAN KALIGESING, KABUPATEN PURWOREJO) - Rubiyanti, Novi; Zulfanita, Zulfanita; Rinawidiastuti, Rinawidiastuti (Jurnal Peternakan Nusantara, 2022)
The Kaligesing goat is very popular among breeders because it is one of the strains of the Ettawa Peranakan (PE) family which has advantages in adaptability, high production and reproduction. The marketing of the Kaligesing Goat does not only occur in the animal market, but there are also buyers who come to the farmer's house. Merchants who are involved in marketing the Kaligesing Goat will form a marketing channel. The length of the marketing channel will affect the cost, margin and share of the price received by the Kaligesing Goat breeder (farmer's sahre). Research was carried out in August at Pandanrejo, Kaligesing, Purworejo. The purpose of this research is to know: (1) marketing pattern of Kaligesing goat; (2) the magnitude of the cost and the margin of each marketing channel; (3) knowing the large portion of the price received by Kaligesing goat breeder. This study involves qualitative descriptive methods. Research results are described in a descriptive way. The object of this study is a Kaligesing goat breeder who belongs to a small farm group in Pandanrejo, Kaligesing, Purworejo. The sampling technique used was the saturated sampling for the breeder and snowball sampling for the traders. The variable of this study is the pattern of marketing channels, the cost and margin of marketing of each marketing channel and the share of the price the breeder receives. Research shows that there are three marketing channel of Kaligesing goat in Pandanrejo: (1) breeder - consumer (2) breeder - traders - consumer (3) breeder - traders - retailers - consumer. The marketing channel that has the highest cost is channel III. The lowest margin is on channel I and the highest on channel III. The price passage received by the Kaligesing goat breeder highest is on marketing channel 1, while the breeder' share lowest is on channel III. Keywords: Kaligesing goat, channel, margin, price